Oxidative Stress in Chronic Hepatitis C: The Effect of Interferon Therapy and Correlation with Pathological Features - Fátima Serejo; Ingrid Emerit; Paulo Manuel Filipe; Afonso Camilo Fernandes; Maria Adília Costa; João Pedro Freitas; Miguel Carneiro de Moura (Canadian Journal of Gastroenterology)
AIMS: To evaluate the oxidative stress parameters before, during and after interferon treatment.